1988
DOI: 10.1111/j.1439-0523.1988.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Eye Pattern and Seed Coat Colour in Cowpea (Vigna unguiculata [L.] Walp.)

Abstract: The F, progenies of crosses between several cowpea (V. unguicuiata ) lines were investigated for variation of eye pattern and seed coat colour. It was found that three (W, H, O) and five (R, P, B, M, K) maior genes control eye pattern and seed coat colour, respectively. The recessive gene (oo) for restricted eye pattern enables the underlying basic white or cream seed coat colour to be observed. A similar effect is obtained with the recessive gene (n-) for colour expression. The expression of mottling (V), pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 1 publication
3
17
0
Order By: Relevance
“…Our results of seed-coat color and eye pattern are in agreement with Drabo et al [51] who evaluated populations segregating for seed color and seed eye pattern. The results they obtained were basically supporting the findings reported by earlier researchers [24].…”
Section: Discussionsupporting
confidence: 93%
“…Our results of seed-coat color and eye pattern are in agreement with Drabo et al [51] who evaluated populations segregating for seed color and seed eye pattern. The results they obtained were basically supporting the findings reported by earlier researchers [24].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present investigation are in agreement to the findings of Kehinde (2000). However, Drabo et al (1988) reported Non-significant at 5 per cent (P 0.05 = 7.815) level of significance five (R, P, B, M, N) major genes control seed coat colour in cowpea.…”
Section: Resultssupporting
confidence: 82%
“…In a series of F2 populations Spillman (1911) and Harland (1919, 1920) identified genetic factors responsible for color expression, including “ Color Factor ” ( C ), “ Watson ” ( W ), “ Holstein-1 ” ( H-1 ), and “ Holstein-2 ” ( H-2 ). A three-locus system controlling seed coat pattern was established by Spillman and Sando (1930) and was confirmed by Saunders (1960) and Drabo et al (1988), though “ O ” was used in place of “ C .”…”
Section: Introductionmentioning
confidence: 91%